Methodology for the integration of information, communication and automation technologies in housing rehabilitation - Eloy, Sara (2010)
This paper addresses the integration of Information, Communication and Automation Technologies (ICAT) in the dwelling space in order to meet the user’s needs. We describe an ongoing PhD research which deals with the rehabilitation of the existing housing stock in order to fulfil the new needs of dwellers in the current Information Society as well as the impact of the integration of ICAT in dwellings. For this purpose we establish a rehabilitation methodology which enables architects to fulfil the client’s needs and requirements in home automation, from the beginning of the architectural process. This will enable the creation of a compatible and properly integrated ICAT infrastructure in homes,paving the way for ambient intelligence and promoting sustainable strategies at the environmental and social levels.